2006
DOI: 10.1097/01.mlg.0000240858.88538.e1
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the Lateral Mandibulectomy Defect: Management Based on Prognosis and Location and Volume of Soft Tissue Resection

Abstract: When the lateral mandible is resected with an accompanying large soft tissue defect of the neck or face (type 2 or type 3 defect), the reconstructive challenge becomes the determination of how best to cover the planned bony reconstruction or whether to perform only a soft tissue reconstruction. When placed in the context of expected prognosis, the proposed classification system based on the location and volume of the associated soft tissue resection can help guide the reconstructive options for these decisions. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…Simpler local reconstructions can save operative time, but are associated with higher complication rates, which may increase hospital stay, canceling out any financial savings. DELEYANNIS et al showed that co-morbidity was the major factor determining complications and length of hospital stay 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Simpler local reconstructions can save operative time, but are associated with higher complication rates, which may increase hospital stay, canceling out any financial savings. DELEYANNIS et al showed that co-morbidity was the major factor determining complications and length of hospital stay 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Alpert suggested that an adequate zone of firmly attached gingiva is crucial for functional and esthetic long-term results in implant restorative dentistry 1 . Other reports on osseous and osteocutaneous flaps did not address this problem 3,4,5,9,10 . This article describes two patients who developed peri-implant reactive tissue following reconstruction with a free vascularized flap that was controlled using a specific surgical/prosthetic protocol.…”
mentioning
confidence: 92%
“…2 Takushima et al in 2001 proposed an algorithm for mandibular defects reconstruction using a single free flap, proposing for the lateral through and through ones the use of free scapula osteocutaneous flap, associated to a second free flap only in case of extensive soft tissue resection. 3 Deleyiannis et al in 2006 proposed the employment of the free radial forearm osteocutaneous flap, associated to a locoregional flap in case of large skin resections, 4 while Gal et al in 2009 emphasized the use of the free fibula osteocutaneous flap. 5 Although these articles carefully analyze each technique, a comprehensive review of all the techniques employable for these defects reconstruction including indication, advantages, drawbacks, functional, and cosmetic results that can be obtained with single free flaps options, free, and locoregional flaps associations, 6 double free flap approach or the use of free soft tissue flap with or without titanium plate, 7 actually lacks in international literature.…”
mentioning
confidence: 99%